Manifestações da heterose em Phaseolus vulgaris L - de Albuquerque, Marcondes Maurício; Vieira , Clibas (Revista Ceres, 2025)
This study, conducted in Viçosa, Minas Gerais; was done with individual plants at a spacing of 100 x 70 cm, with one plant per hole. It was determined that in P. vulgaris heterosis is manifested principally through an increase in plant dry weight. In some crosses heterosis also resulted in a retardation of maturation, a larger number of pods per plant, a larger number of seeds per plant, increased yield, longer main stems and greater foliar area. The largest degree of heterosis was observed in the cross 11x283 and the least in the cross 11x20. The crosses 11x896 and 11x23 were also outstanding, although somewhat less than x283.